Seed centres to be set up - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
In a bid to boost agricultural production throughout the 16-nation Economic Community of West Africa, the ECOWAS Fund based in Lome, Togo, is planning to establish a US$4 million network of seed production centres to form the nucleus of a vital West...